2020
DOI: 10.12688/f1000research.22909.2
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic efficacy of intravenous nefopam after spine surgery: a randomized, double-blind, placebo-controlled trial

Abstract: Background: The incidence of moderate to severe pain is high among patients undergoing spinal surgery. Nefopam can be used as an adjuvant analgesic postoperatively after spine surgery. The study aimed to assess the analgesic efficacy and side effects of nefopam on 24-hour postoperative morphine consumption after spine surgery. Methods: The study is a randomized, double-blinded, placebo-controlled trial. A total of 96 patients were randomized into 4 treatment groups, 24 each. In group 1, patients received norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…morphine consumption in this study was less in the nefopam group, the result did not reach statistical significance. Our results were in concordance with those of another recent investigation [ 21 ] on the use of nefopam in patients undergoing lumbosacral spine surgery. That study chose a single dose of 30 mg of nefopam, which was given either before the surgical incision or before the end of the operation.…”
Section: Discussionsupporting
confidence: 93%
“…morphine consumption in this study was less in the nefopam group, the result did not reach statistical significance. Our results were in concordance with those of another recent investigation [ 21 ] on the use of nefopam in patients undergoing lumbosacral spine surgery. That study chose a single dose of 30 mg of nefopam, which was given either before the surgical incision or before the end of the operation.…”
Section: Discussionsupporting
confidence: 93%
“…Nefopam administration both before the skin incision and upon the completion of surgery failed to exert a discernible influence on the total morphine consumption or the intensity of post-operative pain, as indicated by a study encompassing patients undergoing open spine procedures [19]. In a similar vein, an investigation involving patients subjected to minimally invasive spine surgery unveiled that the incorporation of a 24-hour nefopam infusion did not yield any incremental analgesic benefits or lead to improved functional outcomes post-surgery [20].…”
Section: Discussionmentioning
confidence: 99%
“…This study did not use a weight-based dose as the recommended bolus dose is 20 mg by IV injection and then repeated every 6 hours with a maximum of 120 mg/day [11]. According to a study involving patients undergoing open spine surgeries, nefopam administered before the skin incision and at the end of surgery did not yield any difference in the amount of morphine consumption and the severity of postoperative pain [9]. Similarly, a study involving patients undergoing minimally invasive spine surgery showed that the inclusion of 24-hour nefopam infusion revealed no additional analgesic effect or improved functional outcomes postoperatively [13].…”
Section: Discussionmentioning
confidence: 99%
“…Nefopam could significantly decrease postoperative paresthesia and dysesthesia in patients who underwent endoscopic lumbar discectomy [8]. However, in another study, postoperative morphine consumption was comparable to placebo for open spine surgery [9]. Therefore, this study was designed to evaluate the effects of nefopam on postoperative pain within the first 24 hours, time to recovery, and length of hospital stay (LOS) and assess its opioid-sparing properties in patients undergoing lumbar decompression and fusion.…”
Section: Introductionmentioning
confidence: 99%